MECHANICAL ANALYSIS OF THE SUSPENDED MOTOR SYSTEM - CHEN XiaoYun (Jixie qiangdu)
Mechanical running noise should be controlled in many occasions,the micro ＆ special motor system is one of these. Here,the mechanical analysis of the noise reduction plan of a kind of household vegetable spray system was investigated,the force balance equation was employed to deduce the relation between the suspension line deflection angle,the suspension line length,the moment of the resistance and other parameters,and the tension force of the suspension line was given; the methods and formulae of computing the spring stiffness coefficient and the weight were also obtained,an example was given to illustrate the variations of the moment of resistance and the spring stiffness coefficient to the suspension line deflection angle respectively,and the numerical iteration method was employed to compute the suspension line deflection angle with known moment of resistance,the results showed the feasibility of the method. The methods introduced here have significant conferences to further discussions on the system dynamic vibration and noise control.